The Medici [videorecording (DVD)] : godfathers of the renaissance - Hardy, Justin; Marinoni, Massimo (PBS Home Video, 2005)
A tale of one family's ambition and of Europe's struggle to emerge from the ravages of the Dark Ages. The Medici used charm, skill, and ruthlessness to garner unparalleled wealth and power, ruling Europe for more than 300 years.